Tinjauan Sistematis: Resiliensi Kerja dan Kesejahteraan Psikologis pada Tenaga Layanan Medis Pra-Rumah Sakit - Yoga Dion Pratama; Rubiyanti Rubiyanti; Alimatus Sahrah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Pre-hospital emergency medical services personnel work in high-pressure environments, facing repeated exposure to critical incidents and rapid, high-stakes decision-making processes. These conditions increase the risk of psychological distress, burnout, and impaired performance, emphasizing the need to identify factors that support mental health in this population. Although resilience and psychological well-being have been studied in general healthcare contexts, evidence specifically addressing pre-hospital personnel remains limited and fragmented, hindering the development of tailored interventions for this group. This article presents a systematic literature review examining the relationship between work resilience and psychological well-being among prehospital healthcare professionals. Peer-reviewed articles, academic books, and other scholarly sources were identified through structured database searches using pre-defined keywords. Studies involving physicians, nurses, midwives, ambulance drivers, and call center operators were included based on the established selection criteria. Data were synthesized using thematic content analysis to identify the recurring concepts and interconnections. The findings showed that work resilience is reinforced through stress-management strategies, social support, positive cognitive and emotional reframing, and maintaining physical and mental health. Psychological well-being is enhanced by interpersonal support, solution-focused coping, emotion regulation, and structured psychological programs. Organizational factors, including ongoing training, optimized workload and shifts, and employee recognition, further promote mental health. The implications of these findings highlight the need for healthcare institutions to embed resilience-building initiatives and comprehensive psychological support systems into workforce policies to reduce burnout risk, strengthen employee capacity, and enhance the effectiveness and sustainability of pre-hospital emergency care delivery.